Pendampingan Belajar Matematika Bagi Anak Panti Asuhan Kasih Ibu Aceh Tengah - Bettri Yustinaningrum; Leni Agustina Daulay (AMMA : Jurnal Pengabdian Masyarakat, 2026)
Children at the Kasih Ibu orphanage require educational attention, particularly in mathematics. Without adequate guidance and support, they will struggle to grasp basic mathematical concepts. These fundamental mathematical concepts serve as the foundation for higher education. Guidance and support are essential for learning. The community service approach used is a participatory approach with a mentoring model. This service is divided into three stages: preparation, implementation, and evaluation. Observations during the mentoring process revealed a positive response in terms of participation, motivation, and participant responses. With the mentoring, participants demonstrated positive changes compared to before the mentoring.